Learning programming on mobile phone - Tan, Clement Wee Seng (2014)
This project is about developing a mobile platform for programming learning. The reason for creating this application is to resolve the issue of using traditional programming language pattern and also due to the inefficiency of having lecturer teaching student through lecture ,tutorial and lab. The mobile application is developed using different software such as Android Studio programmed by Java and Mobile programming language.